An alternative model for community education: town government sponsorship - Arsenault, Cynda Collins, author; Porter, Charles F., advisor; Bruner, Howard, committee member; Luchsinger, Leland, committee member (Colorado State University. Libraries, 1983)
Community education, as conducted by community schools has continually expanded its scope and philosophy since its inception in the 1930's as an "after school program". There are many examples of successful community education programs in which the schools have truly become "community schools" with citizen involvement and interagency cooperation. These schools bring enrichment to their programs and enhance the quality of life for those they serve. This research presents the hypotheses that non-school based programs can be developed which use the tools and concepts of community education to enhance the quality of life in their communities. The review of literature found strong support for the necessity of and potential for an expansion of the community education philosophy. A model was developed in the Town of Superior, a small community without a local school. Under the sponsorship of the Town Council, the "Superior Community Involvement Program" (S.C.I.P.) was developed. The purpose of the S.C.I.P. was to "develop a sense of community and improve the quality of life in Superior. This was done by using community resources to provide opportunities for residents of all ages to work, study and play together for self and community improvement". The program was directed by a citizen's advisory council, the "Superior Community Involvement Committee" (S.C.I.C.) and a Coordinator. Funding existed through an internship program and various grants for the salary of the Coordinator. Operating money was obtained by various fundraisers. The success of the program shows that, indeed, community education can be well utilized by a small town without a school. It also opens questions for further exploration as to other potential uses for the community education concept.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Community and school -- Colorado -- Superior; Colorado -- Superior